Assessing Green Resorts Attributes Performance on Tourists ‘S Emotional Intelligence and Future Behavioural Response (S/O 14576) - Nor Azam, Nor Rabiatul Adawiyah; Zainol, Noor Azimin; Rashid, Basri; Mokhtar, Muhammad Fauzi (UUM, 2020)
The success of the hospitality industry largely depends on the environmental condition and its maintenance. The travellers travel to other countries in order to experience the exotic and unpolluted environment, such as the flora and fauna, islands, wildlife, natural scenery, and national forests. Nevertheless, the hospitality industry especially hotels and resorts, has major socio-environmental consequences. Firstly, the rapid development and construction of hotels and resorts can be rather uncontrolled without proper planning, resulting in air, land, and water pollution through the release of dust, runoff, and debris to the environment. Secondly, the daily business operations of hotels and resorts contribute to sewerage and waste with high consumption of resources, such as water, gas, and electricity (Kasim, 2004).